PATH-47. THE 2016 WHO CLASSIFICATION AND IT'S CLINICAL IMPACT: THE LEEDS TEACHING HOSPITALS NHS TRUST EXPERIENCE. (12th November 2021) - Kalra, Neeraj; Geng, Zhuowen; Bailey, Helen; Dony, Alna; Chakrabarty, Aruna; Roberts, Paul; Mathew, Ryan
Abstract: INTRODUCTION: In 2016 the WHO Classification of Tumours of the Central Nervous System was updated to include molecular testing, in addition to the previous standard histological methods; producing a final integrated diagnosis. Although molecular information can guide treatment and aid in prognostication, it adds a significant workload to pathology and genetic testing services. Delayed diagnosis can also add anxiety to patients, at an already traumatic time. AIMS: To determine if final integrated diagnoses, for patients undergoing neurosurgery for CNS tumours, is being provided in an appropriate time frame, and whether it changes clinical management. METHODS: All patients >16 years at the time of surgery with a histopathologically-confirmed CNS tumour were identified from 2016-2020. A retrospective analysis of the time taken to produce an integrated histological diagnosis took place, using the date of surgery and date of verified final integrated report being the first and last data points respectively. Data were collected by accessing electronic and paper health records, and local databases. Changes in clinical management between the initial histology result and the final integrated diagnosis were classified as no change or a major change. RESULTS: 1390 surgical procedures for CNS pathology were identified between 2016-2020, producing 361 final integrated diagnosis reports. 64 (18%) of these reports resulted in a major change in clinical management when compared to the initial histology report. The turn-around time for initial histology from date of surgery was a mean of 9 days and a mean of 34 days for the final integrated diagnosis. CONCLUSIONS: The integrated diagnosis is essential for providing the gold standard of treatment for patients, although for the majority of patients it does not change their clinical management. Further study and discussion is required about the role of the final integrated diagnosis in the management of patients with CNS tumours.